Editorial - Svatoňová, Kateřina (Iluminace, 2011)
Introduction to the following group of articles on the topic of Media Archaeology in the Postmedia Age. A basic introduction to the concepts, issues and main ideas of each contribution.
Keywords: media; media development; film science and research